Engineering in the Production of Crystal Coconut Sugar Enriched with Vitamin A and its Preference Tests for Consumers - Mustaufik Mustaufik (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2023)
Coconut sugar is a food product that has the potential to be fortified with Vitamin A. This study aims to assess the quality of crystalline coconut sugar with vitamin A and test its preference for consumers. The experimental design used Split Plot Design with two treatment factors and 4 replications. The first treatment as the Main Plot (Main Plot) is the type of raw material for crystalline coconut sugar, which consists of 2 variations, namely: M1 = pure sap, and M2 = printed coconut sugar + 5% granulated sugar. The second treatment as a sub-plot was the proportion between palm oil as a solvent and carrots as a source of carotene (Vitamin A), which consisted of 3 variations, namely: S1= 1 : 1 (v/b), S2 = 1 : 2 (v/b), and S3= 2 : 1 (v/b). Physicochemical data were analyzed by F test and followed by 5% DMRT test, while organoleptic properties data were analyzed by Friedman test and followed by multiple comparison test. The best treatment was analyzed by the effectiveness index method. The results showed that a good raw material for producing crystalline coconut sugar with low reducing sugar content and high sucrose content was pure coconut sap. The proportion between palm oil and carrots which can produce crystalline coconut sugar with high levels of carotene (pro vitamin A) is 1 : 2 (v/b). The treatment combination that can produce crystalline coconut sugar with vitamin A with quality according to SNI-SII No.0268-85 is the treatment of the type of raw material for crystalline coconut sugar from pure coconut sap and the proportion of palm oil as a solvent with carrots as a source of carotene 1 : 2 ( v/b). This combination of treatments produced crystalline coconut sugar with physicochemical and organoleptic properties as follows: carotene content of 9.015 mg/100g of material or the equivalent of 752 RE (Retinol equivalent), water content of 3.617 percent, total sugar content of 81.071 percent, sucrose content of 75.627 percent, sugar content 5.434 percent reduction, 0.753 percent ash content and 0.197 percent water insoluble material content,